Effects of hand weeding strip and nitrogen fertilizer on corn plants - Silva, João Renato Vaz da [UNESP]; Martins, Dagoberto [UNESP]; Cardoso, Leonildo A. [UNESP]; Carbonari, Caio Antonio [UNESP] (My University, 2005)
The objective of the present research was to evaluate effects of different strip weed control associated with nitrogen fertilizer on corn applied after planting. The experiment was set and conducted in Botucatu, São Paulo State, Brazil, and the hybrid planted was Dekalb 333-B. A completely randomized block design with four replications was used. Experimental plots were disposed as a factorial scheme 2 x 2 x 4, constituted by two types of weeding on row (with or without manual hoeing), two types of weeding on inter-row (with or without manual hoeing), and four nitrogen levels applied after planting (00, 60, 90, and 120 kg ha-1). Plots were composed by six rows with 5 m length. Nitrogen fertilizer was applied at 35 days after emergence (d.a.e). For weed community it was evaluated: weed density, dominancy, frequency, and relative importance. The main weed species were: Brachiaria plantiginea, Amaranthus retroflexus, Bidens pilosa, Cyperus rotunds, Brachiaria decumbens, Euphorbia heterofila, Oxalis latifolia, Acanthospermum hispidum, Commelina benghalensis. It was evaluated corn height at 40 and 100 d.a.e., first ear insertion height at 100 d.a.e., and final grain yield at harvesting. Plants and first ear insertion height were affected when nitrogen fertilizer was not applied. Treatments without weed control showed that weed interfered negatively with plants height. There were no correlation between weeds and nitrogen fertilizer for all parameters evaluated. Parcels without weed showed the highest ear weights and final grain production. Treatments that received nitrogen fertilizer, independently of studied arrangement, provided higher yields.
Keywords: Competition; Interference; Zea mays; Cultivation; Grain (agricultural product); Harvesting; Nitrogen fertilizers; Weed control; Grain production; Weeding; Plants (botany); nitrogen fertilizer; competition (ecology); fertilizer application; mechanical control; nitrogen; weed control; Acanthospermum; Amaranthus; Bidens pilosa; Brachiaria; Commelina; conference paper; controlled study; corn; crop management; crop production; Cyperus; Euphorbia; harvest; nonhuman; Oxalis; plant height; weed; Agriculture; Biomass; Fertilizers; Nitrogen; Pest Control; Population Dynamics; Grain; Planting; Plants; Weed Control; Weeds; Brazil; Sao Paulo [Brazil]; South America; Western Hemisphere; World; Acanthospermum hispidum; Amaranthus retroflexus; Commelina benghalensis; Cyperus rotundus; Euphorbia heterophylla; Oxalis latifolia; Urochloa brizantha